Crime reporting as storytelling in Persian/Farsi news journalism – perspectives on the narrative function. (3rd May 2016) - White, P.R.R.; Makki, Mohammad
Abstract : This paper is concerned with the nature of storytelling and how different types of story or narrative might be classified and characterised by reference to their generic structures and ultimate social functions. More specifically, it is concerned with Persian/Farsi-language reports of crimes in Iranian newspapers. It describes and analyses the various ways in which these texts are organised structurally, informationally and with respect to "newsworthiness", the various ways in which they deal with chronological sequence and the various ways in which they position the reader attitudinally vis-à-vis the events described and/or their protagonists. In so doing, it provides insights into the similarities and differences between these instances of Persian/Farsi journalism and what the journalism studies literature has presented as "typical" of modern news reports in English and other languages. It also provides insights into the nature of these Iranian crime reports as instances of storytelling or narrative, proposing that taxonomies of the different subtypes of storytelling outlined in the Sydney Genre School literature should be refined to accommodate the modes of storytelling observed in the authors' data set of crime reports.